GenAI Adoption, Academic Integrity, and Responsible Use Among First-Year Accounting Students - Mahardika, Dava Hisyam; Herlani, Irene Sofia; Putri, Uzy Faktihati Arista; Rifalia, Sephanya; Nurul, Helanda; Nurhaini, Nabila Kurnia; Herlambang, Aditya Rizky; Oghenero, Ikolo Robert (Journal of Strategic Behaviour Accounting, 2026)
Generative artificial intelligence (GenAI) has rapidly become part of students' learning experiences, yet little is known about how first-year university students perceive and use these technologies responsibly. This study investigates GenAI adoption among first-year undergraduate students by examining four key dimensions: learning benefits, risks and dependencies, academic integrity intentions, and responsible use. A quantitative survey was conducted with 260 first-year students from Indonesian universities using a validated 25-item Likert-scale questionnaire. Data were analysed through descriptive statistics, Pearson correlation, one-way ANOVA, and multiple linear regression. The findings reveal that students generally hold positive perceptions of GenAI while remaining aware of its potential risks. Academic integrity intentions emerged as the strongest predictor of responsible GenAI use, whereas learning benefits showed a smaller but significant positive effect. Students who used GenAI more frequently also reported greater perceived learning benefits, while no significant gender differences were identified. These findings emphasise that promoting academic integrity alongside AI literacy is essential for encouraging responsible GenAI use and offer practical insights for higher education institutions seeking to integrate AI into teaching and learning responsibly.